Debt maturity determinants in Brazil: evidence from private and public corporate borrowings - Albuquerque, Letícia Gera Gouvêa de (2015)
This study provides an empirical investigation of the determinants of long-term debt maturity in Brazil. We built a unique database that includes privately placed debt and public debt for 308 publicly traded, non-ﬁnancial Brazilian companies, from 2009 to 2013. We perform GMM panel analyses using as dependent variables the amount of long-term debt payable in more than one, three, and ﬁve years for total debt, BNDES (Brazilian Development Bank) debt and corporate bonds. The results show that the BNDES ﬁnances less risky ﬁrms, i.e., those that are larger, older, more tangible and more transparent. We also ﬁnd support for information asymmetry theories, as companies with higher transparency levels have similar leverage levels relative to others but higher proportions of long-term debt in their capital structures. Regarding debt levels, we ﬁnd that more levered companies are larger, less proﬁtable, more tangible and have fewer growth opportunities. To our knowledge, this is the ﬁrst paper to address the determinants of long-term debt maturity in Brazil that uses various speciﬁcations of long-term debt and that examines diﬀerent types of debt.